Method and device for indicating adsorption saturation degree of heavy metal ions

By using the composite membrane of the silk fibropeptide-anthocyanin nanocomposite and cellulose filter paper base, the degree of adsorption saturation of heavy metal ions is determined by using color changes, and the problem of difficulty in accurately determining adsorption saturation in the prior art is solved, and efficient and convenient heavy metal ion removal and membrane replacement tips are achieved.

CN119757331APending Publication Date: 2025-04-04JIANGSU WEIGUANG BIOTECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510028855.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to accurately determine whether the filter material has saturated the adsorption of heavy metal ions, resulting in trouble with membrane replacement.

Method used

The silk fibropeptide-anthocyanin nanocomposite/cellulose filter paper base composite membrane was used to determine the adsorption saturation degree of heavy metal ions by color change. The initial color was pink, and after adsorption saturation, it became dark purple, reddish brown, blue-purple, purple or blue.

Benefits of technology

The visual judgment of the degree of adsorption saturation of heavy metal ions is achieved, the efficiency and convenience of filtration and adsorption methods are improved, and the cost is low and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119757331A_ABST
    Figure CN119757331A_ABST
Patent Text Reader

Abstract

The invention discloses a method and a device for indicating the adsorption saturation degree of heavy metal ions, which are characterized in that a silk fibroin peptide-anthocyanin nanocomposite is anchored on cellulose filter paper, so that the removal effect of the filter paper on the heavy metal ions in a water body is improved; meanwhile, the adsorption of the composite membrane on the heavy metal ions is indicated to be saturated based on different color reactions of anthocyanin and different metal ions, so that the adsorption of the heavy metal ions in the liquid is quicker, and the composite membrane is particularly suitable for removing the heavy metal ions in the liquid with dominant pollution heavy metal ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental detection, and in particular relates to a method and a device for indicating the adsorption saturation degree of heavy metal ions. Background Art

[0002] With the rapid development of industry and the continuous advancement of urbanization, heavy metals (such as cadmium, copper, lead and mercury) are discharged into water bodies in large quantities through rainwater scouring, river transportation and other means during mining, industrial production, agricultural fertilizer and pesticide implementation, causing heavy metal pollution in water bodies, posing a serious threat to human health. These heavy metals pose a serious threat to the ecological environment and human health. Heavy metal pollution in water bodies (such as copper pollution and iron pollution) can seriously change the color and turbidity of water bodies, causing water quality degradation, algae death and collapse of water ecosystems. Some heavy metals can form more toxic heavy metal organic compounds in the body after being ingested by aquatic plants. For example, trace amounts of mercury in water will be converted into more toxic methylmercury after being ingested by microorganisms. After being absorbed by aquatic animals, heavy metals will destroy enzyme protein activity and cause abnormal physiological activities, leading to chronic poisoning or even death. Heavy metals are enriched in the environment and are difficult to degrade. They accumulate and amplify through the food chain, eventually causing serious impacts on human health. Similar to aquatic animals, heavy metals can interact strongly with proteins and various enzymes in the human body, making them inactive, and may also be enriched in certain organs of the human body. If the limit that the human body can tolerate is exceeded, it will cause organ dysfunction, chronic poisoning and subacute / acute poisoning, and even cause digestive system, excretory system, respiratory system, nervous system disorders and cancer, causing great harm to the human body. For example, Minamata disease and osteomalacia in Japan are caused by mercury pollution and cadmium pollution, respectively. Abnormal copper content or metabolism in the human body can cause many diseases, such as diabetes, coronary heart disease, osteoporosis and immune system diseases. In view of the current status of heavy metal ion pollution in water bodies and its harm to the environment and human health, it is particularly important to develop effective methods and devices for the removal of heavy metal ions from water bodies. These methods and devices should not only be able to efficiently remove heavy metal ions in water bodies and reduce their impact on the environment and human health, but also have the characteristics of low cost, simple production and use, and no secondary pollution.

[0003] At present, the methods for removing heavy metal ions from water bodies include chemical precipitation, oxidation-reduction, ion exchange, electrochemical method, adsorption, microbial method, gas hydrate method and filtration method. Chemical precipitation, oxidation-reduction and electrochemical methods will produce a large amount of sludge, which may cause secondary pollution. Among them, the electrochemical method is also costly. The ion exchange method is not only costly, but also complicated to operate, and may also cause secondary pollution. For the microbial method, the relationship between the microbial antibody system and its ability to repair heavy metal ions is still unclear and needs further study. The hydration law has slow kinetics, and thermodynamic conditions and effective separation are still challenges, and the requirements for hydrates and promoters are strict. Compared with the above methods, the filtration method has the advantages of no secondary pollution, simple operation, mature technology, and applicability to water treatment facilities of different scales, but its effect of removing metal ions depends on the removal efficiency of the membrane for heavy metal ions, and it is impossible to accurately judge when the membrane reaches saturation in the adsorption of metal ions, which causes trouble for the replacement of the membrane. Therefore, there is an urgent need for a method to indicate the saturation degree of adsorption of heavy metal ions by the filter material. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for indicating the adsorption saturation degree of heavy metal ions.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for indicating the saturation degree of heavy metal ion adsorption, characterized in that: it includes judging the saturation degree of heavy metal ion adsorption according to the color change of the nanocomposite device, the initial color of the device is pink, and the device turns into dark purple or reddish brown or bluish purple or purple or blue after the heavy metal ion adsorption is saturated.

[0008] As a preferred embodiment of the method of the present invention, the heavy metal ions are iron ions, chromium ions, zinc ions, aluminum ions, copper ions, or ferrous ions.

[0009] As a preferred embodiment of the method of the present invention, the device is dark purple after saturation adsorption of iron ions or ferrous ions; the device is reddish brown after saturation adsorption of complex ions; the device is blue-purple after saturation adsorption of zinc ions; the device is purple after saturation adsorption of lead ions; and the device is blue after saturation adsorption of copper ions.

[0010] As a preferred embodiment of the method of the present invention, the device comprises a silk peptide-anthocyanin nanocomposite / cellulose filter paper substrate composite membrane and a composite membrane adsorption saturation judgment card.

[0011] As a preferred embodiment of the method of the present invention, the silk fibroin peptide-anthocyanin nanocomposite / cellulose filter paper substrate composite membrane is in a wet state or a dry state after freeze-drying.

[0012] As a preferred embodiment of the method described in the present invention, the silk peptide-anthocyanin nanocomposite / cellulose filter paper base composite membrane is prepared by injecting a silk peptide-anthocyanin nanocomposite solution into filter paper, wherein the filter paper is at least one of a cellulose filter material, a soybean fiber filter material, a mineral fiber and a plant fiber mixed filter material.

[0013] As a preferred embodiment of the method of the present invention, the silk fibroin peptide-anthocyanin nanocomposite solution comprises a silk fibroin peptide stock solution, anthocyanin stock solution and deionized water.

[0014] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a device for indicating the saturation degree of heavy metal ion adsorption, characterized in that: the method comprises:

[0015] Prepare silk peptide stock solution and anthocyanin stock solution;

[0016] The silk peptide stock solution, anthocyanin stock solution and deionized water are mixed evenly, and the pH is adjusted to prepare a silk peptide-anthocyanin nanocomposite solution;

[0017] The silk peptide-anthocyanin nanocomposite solution was injected onto the filter paper, so that the solution was evenly distributed on the filter paper and the filter paper was covered with the solution.

[0018] As a preferred embodiment of the preparation method of the present invention, the concentration of the silk fibroin peptide is 0.5-1.5 mg / ml, and the concentration of anthocyanin is 0.1-0.3 mg / ml.

[0019] As a preferred embodiment of the preparation method of the present invention, wherein: the pH is adjusted, wherein the pH is adjusted to 4.0±0.03.

[0020] Beneficial effects of the present invention:

[0021] (1) Low manufacturing and use costs. The silk peptide-anthocyanin nanocomposite / cellulose filter paper base composite membrane is composed of silk peptide, anthocyanin, and cellulose filter paper. Silk peptide comes from the waste of the silk reeling industry. China's silk reeling industry is extremely developed, so silk peptide is abundant and cheap. Anthocyanin is commonly found in the flowers, leaves, fruits, and seeds of plants, with abundant sources and a mature market for material extraction and preparation processes. The solvent used in the formation of the silk peptide-anthocyanin nanocomposite is deionized water. Cellulose is the most abundant natural organic matter on earth. The manufacturing source of medium-speed qualitative filter paper made of cellulose is abundant, and the manufacturing process and industrial chain are also very mature, so the price is low. The solvent used in the formation of the silk peptide-anthocyanin nanocomposite is deionized water. The manufacturing process does not require the use of other chemical reagents and other resources, and the demand for electricity is not high. The preparation of silk peptide-anthocyanin nanocomposite and cellulose filter paper can be carried out in batches. The composite membrane can treat wastewater containing metal ions by adsorption or filtration. After treatment, no large amount of sludge will be generated to cause secondary pollution. Therefore, compared with the currently mature chemical precipitation method, redox method, ion exchange method and electrochemical method, the use of silk peptide-anthocyanin nanocomposite / cellulose filter paper base composite membrane has the advantages of low manufacturing and use costs.

[0022] (2) High efficiency. It not only strengthens the adsorption of metal ions by ordinary cellulose filter paper, but also can judge on site whether the adsorption of metal ions by the composite membrane has reached saturation and the main types of metal ions adsorbed, which can improve the efficiency and convenience of membrane filtration and adsorption methods. Silk peptide has a good embedding effect on anthocyanins. Cellulose is a polymer with strong surface polyhydroxyl polarity. When the solution to be filtered containing metal ions passes through the composite membrane formed by the silk peptide-anthocyanin nanocomposite and cellulose filter paper, most of the metal ions will be adsorbed by cellulose and silk peptide first. When the adsorption of metal ions by cellulose and silk peptide is close to saturation, the metal ions and anthocyanins combine to change the color of the composite membrane. The color change varies with the type of metal ions. Therefore, the composite membrane can be quickly judged to have reached saturation through the change of the color of the composite membrane, prompting the experimenter to replace it. It can be seen that the composite of silk peptide-anthocyanin and cellulose filter paper not only improves the removal efficiency of filter paper for metal ions, but also visualizes the saturation of membrane adsorption, making filtration or adsorption using membrane easier.

[0023] (3) Low carbon and environmentally friendly. The two components of the silk peptide-anthocyanin nanocomposite that form the reinforcing agent, silk peptide and anthocyanin, are naturally degradable substances. The base material, cellulose filter paper, is also taken from nature and can be degraded under natural conditions. There is no large amount of sludge generated during its use. Therefore, the preparation and use of the silk peptide-anthocyanin nanocomposite has little potential harm to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0025] Figure 1 The experimental data is used as the basis for establishing the composite membrane adsorption saturation judgment card.

[0026] Figure 2 It is the measurement result of comparative example 3 of the present invention. DETAILED DESCRIPTION

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0030] Sources of raw materials used in the present invention: Silk peptide was purchased from Hangzhou Linran Biotechnology Co., Ltd., with an average molecular weight of 500-30000 Da, and its parameters are: properties: white or off-white powder; pH: 4.5-6.5; total nitrogen: ≥14.5%; loss on drying: ≤5.0%; residue on ignition ≤3.0%. Anthocyanin was purchased from Beijing Putian Tongchuang Biotechnology Co., Ltd., with production batch number 23022710, and its parameters are: properties: dark red dry powder; loss on drying: ≤2.0%; content: 99.27%. FeCl3 and CuCl2·2H2O were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Filter paper was purchased from Fushun Minzheng Filter Paper Factory, model is medium speed 102, and its parameters are: maximum pore size: 15~20 μm; filtration rate: 35~70 s; ash content: 0.15; weight: 80±4 g / m 2 .

[0031] The instruments used in the embodiments of the present invention mainly include a filtration device and an inductively coupled plasma emission spectrometer (ICP-OES). The filtration device consists of a filtration bottle set and a vacuum pump. The filtration bottle set was purchased from Jiangsu Huida Medical Equipment Co., Ltd. The vacuum pump was purchased from Zhengzhou Great Wall Science and Technology Industry and Trade Co., Ltd., and the model is SHB-Ⅲ A type circulating water multi-purpose vacuum pump. The Büchner funnel in the filtration bottle set is a ceramic funnel with a diameter of 8 cm, and the capacity of the filtration bottle is 250 ml. The inductively coupled plasma emission spectrometer (ICP-OES) was purchased from PerkinElmer Co., Ltd. of the United States, and the model is OPTIMA 8000DV.

[0032] Example 1

[0033] This embodiment provides a method and device for indicating the saturation degree of heavy metal ion adsorption, wherein the device comprises a silk peptide-anthocyanin nanocomposite / cellulose filter paper substrate composite membrane and a composite membrane adsorption saturation judgment card;

[0034] The silk peptide-anthocyanin nanocomposite / cellulose filter paper substrate composite membrane can be in a wet state or in a dry state after freeze drying. The composite membrane can be used to treat sewage with dominant polluting metal ions, low chroma and low turbidity.

[0035] Among them, the composite membrane adsorption saturation judgment card includes the original color of the silk peptide-anthocyanin nanocomposite / cellulose filter paper base composite membrane before use and the color after adsorbing six metal ions to saturation; the six metal ions are iron ions, chromium ions, zinc ions, aluminum ions, copper ions and ferrous ions.

[0036] The original color of the composite membrane of silk peptide-anthocyanin nanocomposite / cellulose filter paper substrate is pink. The color of the composite membrane after saturation is different depending on the type of main heavy metal ions adsorbed. According to the color of the composite membrane, it can be judged whether the main heavy metal ion type adsorbed by the composite membrane and the adsorption of heavy metal ions by the composite membrane has reached saturation. The experimental data based on which the composite membrane adsorption saturation judgment card is established are as follows: Figure 1 shown.

[0037] Example 2

[0038] This embodiment provides a method for preparing and using a device for indicating the adsorption saturation degree of heavy metal ions as described in Embodiment 1, comprising the following steps:

[0039] (1) Prepare silk peptide stock solution: Dissolve silk peptide powder in deionized water and vortex for 30 seconds to form a silk peptide stock solution with a concentration of 10.0 mg / ml. The relative molecular weight of silk peptide is 500-3000 Da, and the purity is 99.99%.

[0040] (2) Prepare anthocyanin stock solution: Dissolve anthocyanin powder in deionized water and vortex for 30 seconds to form an anthocyanin stock solution with a concentration of 2.0 mg / ml. Anthocyanin is cyanidin-3-O-glucoside, an anthocyanin extracted from cornflower, with a relative molecular weight of 484.84 and a purity of 99.27%.

[0041] (3) Prepare a silk peptide-anthocyanin nanocomposite solution: Mix the prepared silk peptide stock solution, anthocyanin stock solution and deionized water in a ratio of 1:1:8, then vortex for 60 seconds to fully mix them to form a silk peptide-anthocyanin nanocomposite solution, and then adjust the solution pH to 4.02. In the silk peptide-anthocyanin nanocomposite solution, the concentration of silk peptide is 1.0 mg / ml, and the concentration of anthocyanin is 0.2 mg / ml. Refrigerate the solution after preparation.

[0042] (4) Preparation of silk peptide-anthocyanin nanocomposite / cellulose filter paper composite membrane: Spread a 9 cm diameter cellulose filter paper flat on a clean and dry glass culture dish, and slowly inject 5 mL of the prepared silk peptide-anthocyanin nanocomposite solution onto the cellulose filter paper until the solution is evenly distributed on the filter paper and the filter paper is completely covered by the solution.

[0043] If the lower surface of the filter paper is bulging due to gas, use a clean and dry glass rod to slowly press and expel the air. During the squeezing process, ensure that the surface of the filter paper is intact and undamaged. Immerse the filter paper for 10 min. Then, take out the filter paper and place it in a clean and dry glass culture dish, and use dust-free paper to absorb the floating water on the surface to obtain a silk peptide-flower element nanocomposite / cellulose filter paper base composite membrane. In addition, the same steps were used to treat cellulose filter paper with deionized water to obtain pure filter paper as a control to illustrate the effect of the composite membrane in removing metal ions and its ability to indicate adsorption to saturation through color changes.

[0044] (5) The prepared silk peptide-anthocyanin nanocomposite / cellulose filter paper composite membrane was used for filtration experiments. An iron ion solution with a concentration of 3.125 mM (i.e., 175.00 mg / L) was prepared using FeCl3 and deionized water, and a copper ion solution with a concentration of 200 mM (i.e., 11200.00 mg / L) was prepared using CuCl2·2H2O and deionized water. Both solutions were dispersed evenly by ultrasound to simulate wastewater bodies with iron ions and copper ions as the main heavy metal ions.

[0045] The prepared silk peptide-anthocyanin nanocomposite / cellulose filter paper substrate composite simulated water was used for filtration. The filtration method was suction filtration, and the diameter of the Buffet funnel used for suction filtration was 8 cm. During suction filtration, ensure that the composite membrane and the Buffet funnel are tightly fitted on the bottom and sides, without gaps, to ensure that the simulated water injected into the funnel has been filtered. During the suction filtration, the simulated polluted water injected slowly was drained with a glass rod so that the sewage water was evenly distributed throughout the composite membrane, and the color change of the composite membrane was always paid attention to. When it was found that the color of the composite membrane was consistent with the color of the composite membrane adsorbed iron ions in the composite membrane adsorption saturation judgment card after saturation, it indicated that the adsorption of iron ions by the composite membrane reached saturation, and the injection of simulated polluted water was stopped. The results are shown in Table 1.

[0046] Table 1 Color of the device before and after adsorption of iron ions saturated Metal ions Original color Color after saturation with adsorbed iron ions Ferric ion / ferrous ion Pink (186, 151, 171) Dark purple (95, 76, 119)

[0047] The metal ion content in the filtered aqueous solution was determined by inductively coupled plasma optical emission spectrometry (ICP-OES), and the metal ion removal rate of the composite membrane was calculated using the difference formula. The filtration results are shown in Table 2.

[0048] Table 2 Removal rate of metal ions in polluted water by the device Metal ions membrane Initial concentration (mg / L) After filtration (mg / L) Removal rate (%) <![CDATA[Fe 3+ ]]> Pure filter paper 175.00 124.08 29.10 Composite film 175.00 91.66 47.62 <![CDATA[Cu 2+ ]]> Pure filter paper 11200.00 8880.00 20.71 Composite film 11200.00 8408.40 24.93

[0049] The removal capacity of the composite membrane for iron ions reached 47.62%, which is nearly twice that of pure filter paper. The removal rate of copper ions of the composite membrane was 24.93%, slightly higher than that of pure filter paper. It can be seen that the prepared silk peptide-anthocyanin nanocomposite / cellulose filter paper base composite membrane has a better iron ion removal effect than cellulose filter paper.

[0050] Example 3

[0051] (1) Prepare silk peptide stock solution: Dissolve silk peptide powder in deionized water and vortex for 60 seconds to form a silk peptide stock solution with a concentration of 20.0 mg / ml. The relative molecular weight of silk peptide is 500-3000 Da, and the purity is 99.99%.

[0052] (2) Prepare anthocyanin stock solution: Dissolve anthocyanin powder in deionized water and vortex for 60 seconds to form an anthocyanin stock solution with a concentration of 2.0 mg / ml. Anthocyanin is cyanidin-3-O-glucoside, an anthocyanin extracted from cornflower, with a relative molecular weight of 484.84 and a purity of 99.27%.

[0053] (3) Prepare a silk peptide-anthocyanin nanocomposite solution: Mix the prepared silk peptide stock solution, anthocyanin stock solution and deionized water in a ratio of 5:1:4, and then vortex for 60 seconds to fully mix them to form a silk peptide-anthocyanin nanocomposite solution, and then adjust the solution pH to 4.01. In the silk peptide-anthocyanin nanocomposite solution, the concentration of silk peptide is 10.0 mg / ml, and the concentration of anthocyanin is 0.2 mg / ml. Refrigerate the solution after preparation.

[0054] (4) Preparation of silk peptide-anthocyanin nanocomposite / cellulose filter paper composite membrane: Spread a 9 cm diameter cellulose filter paper flat on a clean and dry glass culture dish, and slowly inject 5 mL of the prepared silk peptide-anthocyanin nanocomposite solution onto the cellulose filter paper until the solution is evenly distributed on the filter paper and the filter paper is completely covered by the solution.

[0055] If the lower surface of the filter paper is bulging due to gas, use a clean and dry glass rod to slowly press and expel the air. During the squeezing process, ensure that the surface of the filter paper is intact and undamaged. Immerse the filter paper for 10 min. Then, take out the filter paper and place it in a clean and dry glass culture dish, and use dust-free paper to absorb the floating water on the surface to obtain a silk peptide-flower element nanocomposite / cellulose filter paper base composite membrane. In addition, the same steps were used to treat cellulose filter paper with deionized water to obtain pure filter paper as a control to illustrate the effect of the composite membrane in removing metal ions and its ability to indicate adsorption to saturation through color changes.

[0056] (5) The prepared silk peptide-anthocyanin nanocomposite / cellulose filter paper composite membrane was used for filtration experiments. An iron ion solution with a concentration of 3.125 mM (i.e., 175.00 mg / L) was prepared using FeCl3 and deionized water, and a copper ion solution with a concentration of 200 mM (i.e., 11200.00 mg / L) was prepared using CuCl2·2H2O and deionized water. Both solutions were dispersed evenly by ultrasound to simulate wastewater bodies with iron ions and copper ions as the main heavy metal ions.

[0057] The prepared silk peptide-anthocyanin nanocomposite / cellulose filter paper substrate composite simulated water was used for filtration. The filtration method was suction filtration, and the diameter of the Buffet funnel used for suction filtration was 8 cm. During suction filtration, ensure that the composite membrane and the Buffet funnel are tightly fitted on the bottom and sides, without gaps, to ensure that the simulated water injected into the funnel has been filtered. During the suction filtration, the simulated polluted water injected slowly was drained with a glass rod so that the sewage water was evenly distributed throughout the composite membrane, and the color change of the composite membrane was always paid attention to. When it was found that the color of the composite membrane was consistent with the color 4 after the composite membrane adsorbed copper ions in the composite membrane adsorption saturation judgment card, it indicated that the adsorption of copper ions by the composite membrane reached saturation, and the injection of simulated polluted water was stopped. The results are shown in Table 3.

[0058] Table 3 Color of the device before and after adsorption of copper ions saturated Metal ions Original color Adsorb saturated color Copper ions Pink (186, 151, 171) Blue (97, 142, 185)

[0059] The metal ion content in the aqueous solution after filtration was determined by inductively coupled plasma optical emission spectrometry (ICP-OES), and the metal ion removal rate of the composite membrane was calculated using the difference formula. The filtration results are shown in Table 4.

[0060] Table 4 Removal rate of metal ions in polluted water by the device Metal ions membrane Initial concentration (mg / L) After filtration (mg / L) Removal rate (%) <![CDATA[Fe 3+ ]]> Pure filter paper 175.00 104.44 40.32 Composite film 175.00 56.18 65.49 <![CDATA[Cu 2+ ]]> Pure filter paper 11200.00 7708.16 39.78 Composite film 11200.00 6832.80 45.55

[0061] The removal capacity of iron ions of the composite membrane reached 65.49%, and the removal rate of copper ions was 45.55%, both higher than that of pure filter paper. It can be seen that the prepared silk peptide-anthocyanin nanocomposite / cellulose filter paper substrate composite membrane has a better iron and copper ion removal effect than cellulose filter paper.

[0062] Example 4

[0063] The difference between this embodiment and embodiment 2 is that the cellulose filter paper in step (4) is replaced by a mineral fiber and plant fiber mixed filter paper, and the remaining steps are the same as those in embodiment 2. The obtained device has similar results to those in embodiment 2.

[0064] Example 5

[0065] The difference between this embodiment and embodiment 2 is that the cellulose filter paper in step (4) is replaced by soybean fiber filter paper, and the remaining steps are the same as those in embodiment 2. The obtained device has similar results to those in embodiment 2.

[0066] Comparative Example 1

[0067] The difference between this comparative example and Example 2 is that the concentration of silk peptide in step (3) is replaced with 0.1 mg / ml, and the other steps are the same as Example 2. The results show that the color changes earlier when the metal ion adsorption saturation test is performed, and the color changes when it is not saturated. This may be because the low concentration of silk peptide makes it impossible to completely embed the anthocyanins, causing the anthocyanins to be partially dispersed in the solution and thus combine with the metal ions too early to change color, thereby losing the function of indicating saturation.

[0068] Comparative Example 2

[0069] The difference between this comparative example and Example 2 is that the anthocyanin concentration in step (3) is replaced with 0.05 mg / ml, and the remaining steps are the same as Example 2. Results The color change was not obvious during the metal ion adsorption saturation test, which may be due to the low anthocyanin concentration that is not conducive to indicating saturation.

[0070] Comparative Example 3

[0071] The difference between this comparative example and Example 2 is that the heavy metal ions are replaced by manganese ions, calcium ions, magnesium ions, sodium ions, and cadmium ions, respectively, and the removal effect of the composite membrane device on these metal ions and the ability to indicate adsorption to saturation through color change are respectively measured. The results are as follows: Figure 2 As shown, it can be seen that manganese ions, calcium ions, magnesium ions, sodium ions, and cadmium ions hardly cause the color of sericin-anthocyanin to change, and the device cannot be used to indicate saturation of manganese ions, calcium ions, magnesium ions, sodium ions, and cadmium ions.

[0072] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for indicating the adsorption saturation degree of heavy metal ions, characterized in that: The method comprises judging the saturation degree of heavy metal ion adsorption according to the color change of the nanocomposite device, wherein the initial color of the device is pink, and the device turns into dark purple, reddish brown, bluish purple, purple or blue after the heavy metal ion adsorption is saturated.

2. The method according to claim 1, characterized in that: The heavy metal ions are iron ions, chromium ions, zinc ions, aluminum ions, copper ions, or ferrous ions.

3. The method according to claim 1 or 2, characterized in that: The device is dark purple after saturation adsorption of iron ions or ferrous ions; the device is reddish brown after saturation adsorption of complex ions; the device is blue-purple after saturation adsorption of zinc ions; the device is purple after saturation adsorption of lead ions; and the device is blue after saturation adsorption of copper ions.

4. The method according to claim 1, characterized in that: The device comprises a silk peptide-anthocyanin nanocomposite / cellulose filter paper substrate composite membrane and a composite membrane adsorption saturation judgment card.

5. The method according to claim 4, characterized in that: The silk fibroin peptide-anthocyanin nanocomposite / cellulose filter paper substrate composite membrane is in a wet state or a dry state after freeze drying.

6. The method according to claim 5, characterized in that: The silk peptide-anthocyanin nanocomposite / cellulose filter paper base composite membrane is prepared by injecting a silk peptide-anthocyanin nanocomposite solution into filter paper, wherein the filter paper is at least one of a cellulose filter material, a soybean fiber filter material, and a mineral fiber and plant fiber mixed filter material.

7. The method according to claim 6, characterized in that: The silk fibroin peptide-anthocyanin nanocomposite solution comprises a silk fibroin peptide stock solution, anthocyanin stock solution and deionized water.

8. A method for preparing a device for indicating the adsorption saturation degree of heavy metal ions, characterized in that: include, Prepare silk peptide stock solution and anthocyanin stock solution; The silk peptide stock solution, anthocyanin stock solution and deionized water are mixed evenly, and the pH is adjusted to prepare a silk peptide-anthocyanin nanocomposite solution; The silk peptide-anthocyanin nanocomposite solution was injected onto the filter paper, so that the solution was evenly distributed on the filter paper and the filter paper was covered with the solution.

9. The preparation method according to claim 8, characterized in that: The concentration of the silk peptide is 0.5-1.5 mg / ml, and the concentration of anthocyanin is 0.1-0.3 mg / ml.

10. The preparation method according to claim 8, characterized in that: The pH is adjusted, wherein the pH is adjusted to 4.0±0.03.

Citation Information

Patent Citations

  • Zinc ion detection test paper and use method thereof

    CN114910473A

  • Method for rapidly detecting iron ions in water body based on polypeptide anthocyanin composite material

    CN115855921A

  • Aluminum ion detection method based on polypeptide anthocyanin composite material

    CN116008259A

  • Method for detecting ferrous ions in water body

    CN116359152A

  • Method for rapidly detecting iron ions in domestic sewage on site

    CN116359153A